Media Representations of Official Declarations and Political Actions in Brazil During the COVID-19 Pandemic - Lopes de Oliveira, Diogo; Moreno, Erick; Lewenstein, Bruce V. (Frontiers in Communication, 2021)
Our case study situates science communication within the interaction of the COVID-19 disease, scientific research about the disease, public statements by relevant officials, media messages, political actions, and public opinion. By studying these interactions in the Brazilian context, we add to the understanding of science communication complexity by studying a context less easily available to the English-speaking research community. Methodologically, we identified key moments in Brazil during the pandemic using tools such as Google Trends, and content analysis of influencers’ Twitter and Instagram accounts and digital newspapers. These episodes are then explored as case studies, using both quantitative and qualitative content analysis of messages to identify message emphasis frames and political agendas. The results introduce issues rarely explored in previous science communication research, especially ones associated with nationalism and political populism and national inequalities of privilege, income, and trust.